Establishing Initial Conditions in Support of Inflation Targeting - Zelmer, Mark.; Carare, Alina; Schaechter, Andrea; Stone, Mark. (Washington, D.C. : International Monetary Fund, 2002)
This paper provides some practical advice on establishing initial conditions in support of an inflation-targeting monetary framework. These conditions are divided into four areas: a mandate in support of an inflation objective and accountability for achieving this objective; macroeconomic stability; a sufficiently well-developed and stable financial system; and effective policy implementation tools. The measures taken by countries to meet these conditions are also reviewed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet